LEGALNOŚĆ ŁADU JAŁTAŃSKO-POCZDAMSKIEGO Z PUNKTU WIDZENIA PRAWA MIĘDZYNARODOWEGO PUBLICZNEGO - Czubocha, Krzysztof (Zeszyty Prawnicze, 2016)
THE LEGALITY OF THE YALTA AND POTSDAM LEGAL ORDER FROM THE POINT OF VIEW OF PUBLIC INTERNATIONAL LAW Summary The Yalta and Potsdam agreements of 1945 created the so-called “new peaceful order” in Europe. The agreements contained three sorts of provisions. The provisions concerning solely the Great Three were legal. The clauses referring to the WW II aggressors were legal as well. However, the provisions referring to third countries which were not aggressors were null and void. Smaller states were forced to confirm the decisions of the Great Three. The problem is that only an aggressor can be forced to sign a treaty. In other cases the use of force causes invalidity of the treaty. In consequence, the Axis powers were punished lawfully whereas Poland lost its eastern territories unlawfully. Finland and Romania were qualified as aggressors, but in fact the Soviet Union acquired their territories first in 1940 as a result of an aggression and the threat of force. Every attempt at opposing the will of the Great Three was quashed. For instance, Polish government-in-exile was deprived of its effectiveness as it opposed the clauses mandating the loss of Polish Eastern territories. The Great Three were in breach of law in case of several provisions. They were not able to fully adhere to international law as one of the aggressors (the Soviet Union) participated in the creation of the post-war legal order. Therefore, the justice was nor fully served as the Soviet Union was not punished for its aggressions of 1939-1940. The consequences of the partially unlawful decisions of the Great Three linger even today causing international tensions particularly in Central and Eastern Europe.